(untitled) (Herald of Journalism, 2019)
The actualization of the topic of “smart cities” is related to the need of urbanization, of overpopulation, and qualitative and quantitative problems in the organization of modern megacities. The goal-setting of this concept included in improving of the quality of life due to the technological cluster and other important elements. The authors of the article analyzed integrated communications in the field of promoting smart cities and implementing media concepts. Media and social networks have a significant impact on the process of creating smart cities, being not just media, but also part of marketing. The purpose of the article is to present the results of studying the processes of media research and media planning, and to study the optimization factors of the existing “smart city” PR campaign in Kazakhstan, and to describe the com-munication tools, media strategies and technologies of this project. The main direction of scientific research is a description of modern methods of promotion and marketing analytics of media and PR campaigns. The authors note that traditional media lose their previ-ous effectiveness, but open way to digital marketing. In this case, digital technologies of targeted and interactive marketing are becoming the most effective and profitable because of their media content. Specific proposals became as the results of the research work in this article which were on the structure and methodology of media planning for the Smart City project in Kazakhstan. Another result of this work is the practical use of the trial run of the advertising and media campaign to test the effectiveness and filtering of excess materials; statistics and reporting of digital analytics; remarketing feedback optimiza-tion, SEO optimization and LTV, etc.